2016
DOI: 10.1136/bjsports-2015-095278
|View full text |Cite
|
Sign up to set email alerts
|

Running retraining to treat lower limb injuries: a mixed-methods study of current evidence synthesised with expert opinion

Abstract: ImportanceRunning-related injuries are highly prevalent.ObjectiveSynthesise published evidence with international expert opinion on the use of running retraining when treating lower limb injuries.DesignMixed methods.MethodsA systematic review of clinical and biomechanical findings related to running retraining interventions were synthesised and combined with semistructured interviews with 16 international experts covering clinical reasoning related to the implementation of running retraining.ResultsLimited evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
110
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 111 publications
2
110
2
3
Order By: Relevance
“…For each study, a total quality score was given based on the information provided. Based on risk of bias assessment scores, studies were classified as high quality/low risk of bias (≥20), moderate quality/risk of bias (17–19) or low quality/high risk of bias (≤16) 20. Higher modified Downs and Black checklist scores indicate less risk of bias than lower scores.…”
Section: Methodsmentioning
confidence: 99%
“…For each study, a total quality score was given based on the information provided. Based on risk of bias assessment scores, studies were classified as high quality/low risk of bias (≥20), moderate quality/risk of bias (17–19) or low quality/high risk of bias (≤16) 20. Higher modified Downs and Black checklist scores indicate less risk of bias than lower scores.…”
Section: Methodsmentioning
confidence: 99%
“…Gait retraining represents another research focus in runners with PFP and aims at modulating forces acting on the PFJ 19. It has been suggested that transitioning from a rearfoot to a forefoot strike pattern can help decrease symptoms and increase functional scores 20 21.…”
Section: Introductionmentioning
confidence: 99%
“…Is gait retraining effective to treat injured runners? Yes, based on very limited evidence from small-sampled studies 3. But is gait retraining better than other interventions, such as an educated return to running or an exercise programme?…”
Section: Recommending Gait Retrainingmentioning
confidence: 99%